The Migration of Human Smooth Muscle Cells In Vitro Is Mediated by Plasminogen Activation and Can Be Inhibited by α2-Macroglobulin Receptor Associated Protein - Wijnberg, Monique J; Quax, Paul H A; Nieuwenbroek, Nancy M E; Verheijen, Jan H (Thrombosis and Haemostasis, 1997)
The plasminogen activation system is thought to be important in cell migration processes. A role for this system during smooth muscle cell migration after vascular injury has been suggested from several animal studies. However, not much is known about its involvement in human vascular remodelling. We studied the involvement of the plasminogen activation system in human smooth muscle cell migration in more detail using an in vitro wound assay and a matrix invasion assay. Inhibition of plasmin activity or inhibition of urokinase-type plasminogen activator (u-PA) activity resulted in approximately 40% reduction of migration after 24 h in the wound assay and an even stronger reduction (70-80%) in the matrix invasion assay. Migration of smooth muscle cells in the presence of inhibitory antibodies against tissue-type plasminogen activator (t-PA) was not significantly reduced after 24 h, but after 48 h a 30% reduction of migration was observed, whereas in the matrix invasion assay a 50% reduction in invasion was observed already after 24 h. Prevention of the interaction of u-PA with cell surface receptors by addition of soluble u-PA receptor or α2-macroglobulin receptor associated protein (RAP) to the culture medium, resulted in a similar inhibition of migration and invasion. From these results it can be concluded that both u-PA and t-PA mediated plasminogen activation can contribute to in vitro human smooth muscle cell migration and invasion. Furthermore, the interaction between u-PA and its cell surface receptor appears also to be involved in this migration and invasion process. The inhibitory effects on migration and invasion by the addition of RAP suggests an involvement of a RAP sensitive receptor of the LDL receptor family, possibly the LDL-receptor related protein (LRP) and/or the VLDL receptor.